Introduction of the composite materials and applications for manufacturing technology - Marsi, Noraini; Mohd Fodzi, Muhammad Haikal; Subramaniam, Lingeshvaran; Abu Bakar, Bachik; Ibrahim, Md Zin (Penerbit UTHM, 2020)
A composite material can be defined as a combination of two materials resulting in better properties than those of the individual's compound used. The two constituents form a matrix and reinforcement. the main advantages of composite materials are their high strength and rigidity, combined with low density compared with bulk materials, which allows a reduction in weight in the finished part...